ANALYSIS OF THE OUTCOMES OF CATHETER-DIRECTED THROMBOLYSIS IN PATIENTS WITH LOWER LIMB ARTERIAL THROMBOSIS INVOLVING OUTFLOW ARTERIES - Dmytro A. Makivchuk; Yurii M. Hupalo; Sergii M. Didenko (Клінічна та профілактична медицина)
Aim. To evaluate the effectiveness of catheter-directed thrombolysis (CDT) in patients with critical lower limb ischemia (CLI) due to thromboembolic arterial occlusions and to study the long-term outcomes of the treatment.